ANALISIS CITRA MEREK, KUALITAS PELAYANAN DAN TESTIMONIAL TERHADAP KEPUTUSAN PEMBELIAN SEPATU VENTELA DI SHOPEE - Alkahvy, Mocca (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
This study aims to examine and analyze the influence of brand image, service quality and testimonials on the decision to purchase Ventela shoes at Shopee. The research approach used is quantitative causality. Of the 1,706 students of the Faculty of Economics and Business who have purchased Ventela shoes at Shopee, the number is unknown, 40 people were sampled from the population using the Roscoe theory. Methods of data collection using a questionnaire. Then tested with multiple linear regression processed with SPSS version 16. The test results that brand image has a significant effect of 0.042 on purchasing decisions, service quality has no significant effect with a value of 0.078 on purchasing decisions and testimonials have a significant effect of 0.014 on purchasing decisions. While brand image, service quality and testimonials influence purchasing decisions simultaneously by 40.8% influenced by other variables not examined by 59.2%.